Socialization Of Processing Of Fishery Products In Saoka Village Maladummes District Sorong City - Sukmawati Sukmawati (Fakultas MIPA Universitas Negeri Padang, 2022)
Abstract – Maladummes district, Saoka village is a coastal area located in the city of Sorong. In the area, natural resources are quite abundant such as catches of fish, squid, shellfish and so on, but they are not utilized optimally because the catch is only sold in fresh form. Whereas in addition to being sold in fresh form, it can also be processed into products so that the selling value increases. This is due to the slow access to incoming information in the surrounding area, due to the low level of education of local residents. Apart from that, people are left behind in the development of technology and important information that has been and is being developed. Such as important information regarding simple appropriate technology that can be applied to produce fishery products, this is because there have never been socialization activities for processing fishery products and other foods. The purpose of this activity is that the people of Saoka village are able to know about the processing of fishery products, so that later the community will be able to apply it in daily life, or make it a business area on a household scale. The method of implementation is by means of lectures and discussions with participants on how to make fish balls, fish nuggets, fish floss, seaweed meatballs and seaweed syrup. The result of the activities that have been carried out is that the people of Saoka village, Maladum district mes, Sorong city, West Papua, responded very well and enthusiastically. This is indicated by the increase in the value of the pre-test and post-test regarding the processing procedures for fishery products. Increased knowledge of partner communities by 41%. Keywords — Socialization, Processing, Products, Fisheries, Saoka Village